MANAJEMEN KURIKULUM DAN SISTEM PENILAIAN KURIKULUM BERBASIS KKNI : Studi Pada Program Studi Agrobisnis Universitas Wiralodra Indramayu - Arwani, Arwani (Jurnal Pendidikan Educandum, 2023)
This study aims to analyze the preparation, implementation and evaluation of curriculum development based on the Indonesian National Qualifications Framework (KKNI) at the Agribusiness Study Program, Wiralodra Indramayu University. This study uses a qualitative approach with descriptive analysis method. Interviews were conducted directly with informants, consisting of the Dean, Deputy Dean, Head of the Agribusiness Study Program. The results of observations and documentation were obtained from various studies of documents, manuscripts, and archives related to the IQF-based curriculum management. The data analysis technique uses data reduction, data display and verification. The results of this study indicate that: a) The curriculum of the Agribusiness Study Program at Wiralodra Indramayu University is in accordance with the applicable KKNI curriculum reference and every component of curriculum management consisting of planning, implementation and evaluation of the curriculum has been going well, although there are still shortcomings and weaknesses of each the process carried out; b) Development of curriculum management must pay attention to SOPs and regulations for the IQF curriculum, but in practice it is still not fully based on the IQF. Keywords: Curriculum Management, Indonesian National Qualifications Framework